Building Digital Trust And Intention To Use The Dana Application Through Financial Literacy And Perceived Credibility - Anggoro, Rifky Dhimas; Sari, Puspa Novita (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Rapid digital technology awareness has brought significant shift to community payment behavior, especially Generation Z, whom widely use digital wallets such as DANA. Although the national financial inclusion rate is high, digital financial literacy remains low, this impacts trust and intention to use fintech services. Research should examine the elements that influence of financial literacy and perceived credibility on intention to use the DANA application, with trust as a mediating variable. The study used a quantitative method with 170 respondents in Surakarta and was analyzed using SEM-PLS through SmartPLS. Outcame showed meaning financial literacy and perceived credibility had a positive also significant effect on trust. Trust also had significant impact at intention to use the application. However, financial literacy did not have a significant direct effect on intention to use the application. Conversely, perceived credibility shows a significant direct effect. In addition, trust proves to mediate the relationship on variables, both fully also partially. Investigation it provides theoretical contributions toward study of digital financial behavior and practical recommendations for fintech service providers to improve user literacy and trust.